Fire spreading across boundaries: The positive spillover of entrepreneurial passion to family and community domains - Xiao, Xiong-Hui; Fu, Hui (Frontiers in Psychology, 2022)
Passion plays a crucial role in entrepreneurial activity, while its positive spillover to the family and community domains is scant. We proposed an integrated enrichment framework of “work-family-community” based on the literature in the field. Drawing upon the matching samples of entrepreneurs' individuals, families, and communities in the China Labor-force Dynamics Survey (CLDS) database, we identified a significant positive spillover effect into the family and community domains and explored the moderating role of the entrepreneur's perceived personal control. The empirical results indicate that entrepreneurs with higher passion experience higher subjective wellbeing related to family members and have a higher likelihood of engagement in prosocial behaviors. Perceived personal control positively moderates the spillover of passion to life and economic satisfaction. The spread of an entrepreneurial role model's peer effect and the contagion of entrepreneurial passion have a significant positive impact on entrepreneurial behavior in a cluster. Synthesizing our findings, we contribute to the literature concerning work-family enrichment, entrepreneurial passion, and the spillover-crossover model and offer important implications for entrepreneurs' role transition tension.